OFF-LABEL AND UNLICENSED PRESCRIBING IN PEDIATRIC INPATIENTS WITH NEPHROTIC SYNDROME IN A MAJOR TEACHING HOSPITAL: AN INDONESIAN CONTEXT - Ramadaniati, Hesty u; Tambunan, Taralan; Khairani, Sondang; Adisty, Happy S (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To estimate the prevalence of off-label and unlicensed prescribing in pediatric inpatients with nephrotic syndrome in a major teaching hospital in Indonesia. Methods: A retrospective study was conducted in study hospital using medical records from pediatric inpatients with nephrotic syndrome during the period of January-December 2015. Patient and prescribing data were collected, and drugs were classified as on-label or off-label/unlicensed based on the Indonesia National Drug Information (IONI). Thereafter, off-label drugs were categorized with a hierarchical system of age, indication, route of administration, and dosage. Results: There were 1553 drugs with 94 different types of drug administered to 67 patients during the study period. The data uncovered that1023 (65.9%) of the drug prescriptions were used either off-label/unlicensed. Most off-label drugs (n=433, 42.4%) were from nondiureticsantihypertensive drugs. The most common drugs used in an off-label/unlicensed manner were prednisolone and lisinopril. The high rate of off-label drug use in children was mainly related to age (n=772, 75.5%). Pediatrics with nephrotic syndrome was vulnerable to off-label uses where every patient received at least two off-label drugs. It seems that off-label prescribing in pediatric with nephrotic syndrome was not influenced by age or gender as every patient received off-label drugs. Conclusion: Despite the high prevalence of off-label use in pediatric patients with nephrotic syndrome, this use is supported by evidence-based prescribing. Further, there remains a need for supporting clinical trials for pediatric drugs and updating IONI as the standard drug information in Indonesia to provide complete product information for pediatric use. Keywords: Off-label drug, Syndrome nephrotic, Inpatient, Pediatrics.